Diseño geométrico y estructural de las vías del sitio Valle Hermoso perteneciente a la parroquia Bella María del cantón Santa Rosa de la provincia de El Oro. - Vega Carrilo, José Gabriel (2015)
There are many problems that must be taken into account in the Valle Hermoso site belonging to the Parish of Bella Maria, as topographic, geological and hydrological aspects and the economic needs of the affected area and potential environmental impacts. The aim of the project is the Geometric Design and Flexible Pavement street Beautiful Site Valley belonging to the Parish of Bella Maria whose total track length is 3.77 km, through the application of software for road design, geotechnical and hydrological we arrive to perform the work by the GAD of Santa Rosa Canton and then facilitate the transportation of goods and people mobility of Valle Hermoso site Bella Maria parish in the province of El Oro. The following methodologies, experimental technical, in this method the soil tests were performed was used; surveying the streets of the site corresponding to 3.77 km, the traffic count was conducted, average daily calculation of which traffic is 300 vehicles (AADT), As a result a road of IV order was obtained, and a CBR design corresponding to 3.65% is; and the thicknesses of the Structural Binder Floor: 5cm wearing course, base 15cm, 20cm Improvement Sub-base 35cm; Total structural package 75cm; and Geometric Design of the 3.77 km road Keywords: geometric design, structural pavement design, environmental impact, budget.